Psychosocial outcomes and peer influences among multiracial adolescents in the United States - Grilo, Stephanie A.; Santelli, John S.; Nathanson, Constance; Catallozzi, Marina; Abraido-Lanza, Ana F.; Adelman, Sarah; Hernández, Diana (Frontiers in Public Health, 2023)
Objective To examine racial and ethnic self-identification among adolescents and explore psychosocial outcomes and peer treatment for multiracial adolescents in the United States. Methods Data are from the 2014 Child Development Supplement, a subsample of the Panel Study of Income Dynamics. Data were weighted to be nationally representative. Descriptive statistics were used to describe the population and to explore family and parent demographics. Multivariable regressions tested for differences in psychosocial outcomes and peer treatment and group behaviors for multiracial youth in comparison to their single race peers. Results Black multiracial youth had significantly lower scores on the children's depression index compared to single race Black youth, and White multiracial youth reported significantly higher rates of peer mistreatment in comparison to White single race youth. Black multiracial and White multiracial adolescents reported similar positive and negative peer group behaviors. Conclusions Complex patterns emerge when examining the psychosocial and peer treatment variables presented in this analysis for multiracial adolescents and their single-race peers. The findings regarding depressive symptoms and peer bullying point to signs of different relationships between multiracial groups. White multiracial adolescents report worse outcomes than their White single-race peers, but Black multiracial adolescents reporting better outcomes than their Black single-race peers.